Software measurement standards for areal surface texture parameters: part 1-algorithms - Harris, P M; Smith, I M; Leach, R K; Giusca, C; Jiang, X; Scott, P (Measurement science & technology, 2012)
Reference software for the evaluation of a set of areal surface texture parameters is described, focusing on the definitions of the parameters and giving details of the numerical algorithms employed in the software to implement those definitions. The main consideration in the design and development of reference software is its numerical correctness, and the algorithms chosen and the implementations of those algorithms reflect this consideration. The surface for which parameters are to be evaluated is a bicubic spline interpolant to the available discretely-sampled data, and parameters are evaluated for that continuous surface either to a high numerical precision or to a numerical precision that is under the control of the user.